Tahlil Al-Akhta Al-Lughawiyyah fi Al-Insya Al-'Araby : Dirasah Halah Bima'hadi Riyadli Al-Ulum wa Ad-Da'wah - Neng Fitria; Riyadi, Agus (Department of Arabic Teaching, STAI PUI Majalengka, 2025)
Riyadlul ‘Ulum Wadda’wah Islamic Institution was one of the Islamic educational institutions concerned with the Arabic language. The students of the second grade were learning the lesson of Insya. This research aims to identify the forms of linguistic errors in the Insya lesson, to know the factors that cause linguistic errors in the Insya lesson, and to know the school's strategy to address linguistic errors in the Insya lesson for second grade students of Riyadlul ‘Ulum Wadda’wah Islamic Institution Tasikmalaya for the academic year 2022-2023 AD. This research is a type of qualitative research using a case study, and the researcher used the method of data collection, which is interview, observation, and testing. The results of this research are that the most mistakes made by the students of the second grade are: grammatical errors, morphological errors, and spelling errors. The students' errors in morphology were 25 sentences, grammatical 72 sentences, spelling 73 sentences, semantic one sentence, compositional 4 sentences and stylistics 5 sentences. Therefore, most of the mistakes made by the students of the second grade are spelling errors.